Stres dan kepuasan kerja guru Pendidikan Khas di daerah Johor Bahru - Raso, Rosni (2014)
This study was aimed to identify the level of stress and work satisfaction among Special Education teachers in Johor Bahru District. The study involved three categories of Special Education Schools that were Special Education for the Learning Impaired, Special Education for the Hearing Impaired and Special Education for the Visually Impaired. One hundred teachers chosen as respondents in this study but only 89 respondents offered their full commitment in this study. Data were collected by questionnaires that consists three areas; part A (Demography), part B (Stress from work) and part C (Work satisfaction). The collected data were analyzed using descriptive statistics (mean and percentage) and inferential statistics (t-test, ANOVA and Pearson correlation). The study results indicated that work stress among Special Education teachers in the Johor Bahru area was moderate (mean=2.768), while the level of work satisfaction was high (mean=3.816). This study also explained that male and female teachers had different perception towards work stress (sig=0.000). The study also showed that work satisfaction among Special Education teachers varied with the length of their service. On the other hand, there was no significant difference in work stress and job satisfaction experienced among the different categories of schools. This study also established a weak association between work stress and work satisfaction among Special Education teachers in Johor Bahru District (r=-0.431). In this study, several suggestions were suggested for the findings of the present study, and for future studies.